Marginal Zone B-Cell Depletion Impairs Murine Host Defense against Borrelia burgdorferi Infection - Belperron, Alexia A. (American Society for Microbiology, 2007)
Marginal zone B (MZB) cells are a B-cell subset that produces T-cell-independent antibodies to blood-borne antigens. In this study, we examined the effects of MZB cell depletion on the immune response to the Lyme disease spirochete Borrelia burgdorferi, an extracellular pathogen for which T-cell-independent antibody is an important host defense. MZB cell depletion of C3H/HeJ mice using monoclonal antibody to LFA-1 and α(4)β(1) integrins reduced B. burgdorferi-specific immunoglobulin M (IgM) titers, enhanced pathogen burden, and led to more severe arthritis assessed within the first 2 weeks of infection. In addition, MZB cell-depleted mice had reduced levels of B. burgdorferi-specific IgG, which correlated with diminished splenic CD4(+) T-cell-activation, proliferation, and cytokine production. Passive transfer of immune mouse serum from infected control mice into infected MZB cell-depleted mice reduced pathogen burden but did not alter the expression of T-cell activation markers on splenic CD4(+) T cells. These findings demonstrate that MZB cells not only are a source of pathogen-specific IgM important for limiting spirochete burden and pathology but also play a prominent role in the priming of splenic T-cell responses to a blood-borne pathogen.